Perception of organizational commitment in students of an art school in Lima - Anaya Figueroa, Tania María (2020)
The research aims to know the organizational commitment in an art school of Metropolitan Lima; it is a descriptive study and the design is non-experimental, cross-sectional with a quantitative approach. The sample was of probabilistic type and was conformed by 201 students who studied between the cycle III and IX of the professional career of teacher in Artistic Education and Professional Artist in the specialty of music and dance. The data collection instrument was a questionnaire adapted from the scale of commitment of Allen and Meyer (1990) and Meyer, Allen (1993), which was validated by expert judgment .97 Aiken's V coefficient. Reliability with the Cronbach's alpha coefficient was .90, considered very high. The results showed that the organizational commitment is between medium and high. At the level of the dimensions, the affective is at a high level and those of continuity and regulations are at medium and high level; the correlation between dimensions shows that the affective dimension shows a positive relationship with the normative and continuity.